PROFIL PERESEPAN OBAT PADA PASIEN DIABETER TIPE2 DI RSUD LABUANG BAJI MAKASSAR PROVINSI SULAWESI SELATAN PERIODE JANUARI DESEMBER 2023 - Djajanti, Agust Dwi Djajanti (Akademi Farmasi Yamasi Makassar, 2024)
Type 2 diabetes mellitus (DM) is a long-term disease that occurs when the body cannot use insulin effectively. Based on previous research data in 2022 for the January-December period, data was obtained on type 2 DM patients who received treatment at Labuang Baji Hospital, Makassar, South Sulawesi Province, as many as 145 people, so for this reason this research was carried out with the aim of knowing the profile of drug prescribing in diabetes patients. type 2 at Labuang Baji Hospital, Makassar, South Sulawesi Province for the period June-December 2023. This research uses descriptive research methods and retrospective data collection. The variables studied in the Type 2 DM drug prescribing profile are type of drug, dose, instructions for use and amount of drug. The total number of recipe data obtained was 125 recipes. The research results show that the most frequently prescribed type 2 DM drug is Glimepiride. The most frequently prescribed doses of type 2 DM drugs are Glimepiride 2mg, Metformin 500mg, Glibenclamide 5mg, Pioglitazone 30mg and Acarbose 50mg and 100mg. The rules for using type 2 DM that are most often prescribed are Glimepiride once a day, Metformin 3 times a day, Glibenclamide once a day, Pioglitazone once a day and Acarbose 3 times a day. The number of type 2 DM drugs most frequently prescribed are Glimepiride 30 tablets, Metformin 60 tablets, Glibenclamide 30 tablets, Pioglitazone 30 tablets and Acarbose 30 tablets.